Central Injection of Endomorphin-2, but not Endomorphin-1, Increases Food Intake in Chicks via μ1-opioid Receptors - Takashi Bungo; Koh-Ichi Dodo; Tomofumi Izumi (The Journal of Poultry Science, 2007)
The endogenous tetrapeptides endomorphin-1 and -2 are potent, selective μ-opioid receptor agonists in mammals. The present study was done to elucidate whether central injection of endomorphins enhances feeding behavior in chicks, and to investigate the interaction with the μ1-opioid receptor. We found that the intracerebroventricular injection of endomorphin-2 (10-30nmol) significantly stimulated food intake in neonatal chicks during the 60-min period postinjection. However, the same doses of endomorphin-1 injected with ICV had no significant effects on feeding behavior. The orexigenic effect of endomorphin-2 was significantly attenuated by the μ1-opioid receptor antagonist naloxonazine. These results indicate that the administration of endomorphin-2, but not endomorphin-1, into the chick brain produces the orexigenic effect through the μ1-opioid receptor.